The Influence of Science Laboratory Management on Increasing Manager Performance at SMA IT Yarsi Mataram - Aldian, Hendy; Wahyudiati, Dwi; Bahtiar, Bahtiar; Alfarisi, Salman (Journal of Research in Education and Pedagogy, 2025)
The aims of this research include exploring the influence of laboratory management on the performance of managers (laboratories) at SMA IT Yarsi Mataram. This research uses a quantitative approach with a correlational type of research. The research method uses statistical research methods with an analytical design. The data collection technique uses observation, which consists of 1 independent variable, namely laboratory management, and 2 dependent variables, namely manager performance and science process skills. There are 2 instruments used, namely a questionnaire instrument for manager performance variables, and an assessment sheet for science process skills. The total population is 78 people, and the sample is 30 people. The research results show that, among other things, there is no influence of laboratory management on manager performance; this can be seen from the significance value obtained from the ANOVA test, namely 0.221, which is greater than the 5% significance level, namely 0.05. This means that the differences or variations in laboratory management are not strong enough to influence changes in manager performance. This could be caused by other factors outside of laboratory management that are more dominant in influencing performance, such as leadership style, organizational culture, work motivation, or the performance appraisal system used. The implication of this study is the importance of the laboratory as a place to develop students’ science skills practically. So, to provide maximum implementation, laboratory management is needed with laboratory assistants who have good performance, so that the final results in science learning can achieve the intended goals.